Long-term outcomes of biodegradable versus 2nd generation durable polymer drug-eluting stents in PCI: Protocol for a systematic review and meta-analysis. - Rosa J Thuemmler; Trisha Choudhary; Yong Hui Tan; Maria-Bianca Andrei; Haipeng Liu; Niraj S Kumar (PLoS ONE)
Background More than 3 million individuals globally experience STEMI each year, with percutaneous coronary intervention (PCI) as the preferred revascularization method. While second-generation Drug Eluting Stents (DES) reduce restenosis compared to bare-metal stents, complications such as neoatherosclerosis and stent thrombosis remain. Second-generation stents, including durable polymer (DP-DES) and biodegradable polymer (BP-DES), aim to improve outcomes, though guidelines do not specify a preference. Given mixed results from prior studies and new long-term data, we aim to perform a systematic review and meta-analysis comparing long-term outcomes of DP-DES vs. BP-DES following PCI. Methods This protocol has been developed following the Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols. MEDLINE, Embase, and Scopus databases will be searched for eligible observational and interventional studies from inception up to 5th of October 2024. Screening (title/abstract and full text), data extraction, risk of bias assessment, and quality of evidence assessment will be conducted by two independent reviewers. A random-effects model will be used to meta-analyse outcomes. Discussion DES have greatly advanced PCI for STEMI. However, long-term stent thrombosis remains an issue due to chronic inflammation and impaired healing from the stent's polymer coating. To overcome this, BP-DES were introduced to dissolve their coating within 2-9 months. However, whether BP-DES offers superior long-term outcomes compared to second-generation DP-DES remains uncertain. While previous meta-analyses have shown similar outcomes, recent studies suggest BP-DES may offer better long-term results. This review will compare long-term outcomes (≥5 years) of BP-DES vs. DP-DES, providing important insights to inform clinical practice. Systematic review registration: PROSPERO (CRD42024592579).